Association of adaptive and maladaptive narcissism with personal burnout: findings from a cross-sectional study - Känel, Roland von; Herr, Raphael; Schmidt, Burkhard (Industrial health, 2017)
Japan's largest platform for academic e-journals: J-STAGE is a full text database for reviewed academic papers published by Japanese societies